Antibacterial and antioxidant properties of bioactive extracts and peptides from Morinda Citrifolia, Annona Squamosa, Alstonia Angustiloba and lactic acid bacteria / Abdulmuhsin Moslim Shami - Shami, Abdulmuhsin Moslim (2014)
Medicinal plants and lactic acid bacteria are used to treat a wide range of disease conditions. The aim of the study was to determine antimicrobial and antioxidant activities of bioactive compounds and peptides from different morphological parts of common medicinal plants namely Morinda citrifolia, Annona squamosa, Alstonia angustiloba, an Australian plant mixture and lactic acid bacteria. In the first part of the study, different methods were used to standardize the extraction of antimicrobial and antioxidant compounds. It was found that methanol extraction of plants tissue showed higher antimicrobial activity than aqueous extracts against the test bacteria Staphylococcus aureus (RF 122), Escherichia coli (UT181), Bacillus cereus (ATCC 14579), Pseudomonas aeruginosa (PA7), methicillin-resistant Staphylococcus aureus (ATCC BA-43) and Helicobacter pylori (ATCC 43504). Furthermore, plant tissues showed significant antioxidant activities using DPPH and SOD assays. GC-MS analysis of extracts revealed bioactive compounds (diterpenes, anthraquinones, alkaloids, organic acids) in these extracts. In the second part of the study, bioactive compounds were fractionated into anthroquinones, alkaloids, diterpenes and phenolic compounds. Anthraquinones extracts from the fruit, leaf and root of M. citrifolia exhibited significant antibacterial activity against all strain of test bacteria. Anthraquinones extracted from the fruit have higher level of antioxidant activities compared to another parts of the plant. IR spectra of the anthraquinones extracts of M. citrifolia indicated the presence of O-H, C=O, C-H groups. A significant morphological change in cell wall, membrane and destruction of B. cereus was observed in the presence of anthraquinones. Alkaloid extracts from the medicinal plants showed antibacterial activity against pathogenic bacteria including MRSA and H. pylori while P. aeruginosa was resistant to alkaloids extracted from M. citrifolia fruit. Alkaloid extracts from A. squamosa leaves have a high level of antioxidant activities. IR spectra of the alkaloid extracts indicated the presence of O-H, C=O, C-H and N-H groups. SEM observations of the action of alkaloids on bacterial cell wall showed rupture and cell lysis. Phenolic compounds extract from plant mixture gave antibacterial and antioxidant activities. Diterpens extracts from A. squamosa fruit had significant antibacterial activity against pathogenic bacteria and MRSA and significant antioxidant activity. SEM observation of the action on bacterial cells showed disruption of cell wall and swelling of the cells. IR spectra of diterpenes and phenolic compounds indicated the presence of O-H, C-H, C=O and C-H groups. LC-MS analysis of bioactive compounds plants identified specific compounds. In the third part of the study, antibacterial peptides extracted from lactic acid bacteria by the acidic methanolic method were shown to have activity against pathogenic bacteria including MRSA and H. pylori and had antioxidant activity. LC-MS analysis of peptide of Lactobacillus paracasei subsp. paracasei 8700:2 identified a novel bacteriocin in this extract. Peptides extracts from the medicinal plants had significant antibacterial and antioxidant activities. LC-MS analysis of Australian plant mixture indicated the presence of Pathogenesis-related protein 2 of Phaseolus vulgaris. SEM and TEM analysis of the mechanism of action of purified peptides from lactic acid bacteria and APM showed membrane disruption with bubble-like formations and cell lysis.